Probability of occurrence of the circular economy model in a company that provides the drinking water service in Cajamarca - Peru (LACCEI, 2024)
The management of water within a population deserves to be examined in order to transform its habitual use in a linear way towards circular processes that contribute to a better channeling and optimization of the resource. In this sense, because water is a resource of the utmost importance and with urgency in its care, the purpose of this research is to study the probability of occurrence of implementing circularity in a company that provides drinking water service in the city of Cajamarca - Peru, considering the evaluation of its three fundamental principles. The study belongs to a correlational descriptive level, applying two data collection instruments to 372 households and 120 collaborators respectively and which in turn constitute the study samples, thus also through econometric models the achievement of the objective was facilitated. The LR statistic equal to 72.57407 and 72.35393 of the Logit and Probit Models for the internal context and 6.862125 and 6.784645 for the external one, respectively, assume that the variables considered as a whole explain the models, confirming this with the high probability of occurrence (88%, 97% and 90% for both contexts) of the development of the Circular Economy in the economic unit under study realistic scenario, however, after carrying out an extensive analysis it is deduced that the current state of the company is still in the initial phase for said purpose, focusing opportunities for improvement and strengthening mainly in the second and third principles of the Circular Economy.